Characteristics of U.S. Agricultural Communications Undergraduate Programs - Jefferson D. Miller; Morgan M. Large; K Jill Rucker; Kate Shoulders; Emily B. Buck (Journal of Applied Communications, 2015)
This study characterized agricultural communications undergraduate programs nationwide. A total of 40 undergraduate agricultural communications programs were identified via the National Agricultural Communicators of Tomorrow database, Internet searches, and previous academic program research, and their existences were verified via multiple sources. Objectives included creating an accounting of existing programs, describing the programs’ demographics, and identifying top programs. This study employed a census approach and used a descriptive survey design, including both quantitative and structured qualitative questions. The quantitative data were analyzed via descriptive statistics. A total of 26 respondents — faculty representing U.S. undergraduate agricultural communications programs — participated in this study. An increase in the number of academic programs across the U.S. was observed, compared to the last similar study published in 2000, suggesting an increase in popularity and student demand, which is most likely a result of an increase in industry demand for agricultural communications graduates. While programs varied in size and age, most faculty respondents projected an increase in enrollment in their undergraduate programs. Future studies characterizing the discipline should be conducted on a more frequent, standardized schedule, and improved participation in the study should be a goal. National curriculum studies also should be conducted to tie program characteristics and instructional methodologies to program success and to correlate program characteristics and demographics.
Keywords: Agricultural communications; academic programs; curriculum development; program development; program evaluation; Association for Communication Excellence Conference